Initial Stages of Electrocrystallization of Coatings with Tin and Tin-Copper and Tin-Copper-Ultradisperse Diamond Alloys - I. I. Kuzmar; D. Y. Gulpa; L. K. Kushner (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The need of modern microelectronics in the development of technological processes for the formation of nanostructured layers puts forward the necessity of understanding the mechanisms of nucleation and growth of deposits. The article considers the features of the initial stages of electrocrystallization of coatings with tin and tin-copper and tin-copper-ultradisperse diamond alloys. The kinetic regularities of electrode processes were studied by the voltammetry method. Based on the experimental data, the nucleation parameters (nucleation energy, eﬀective interphase surface energy, radius and volume of the nucleus) were calculated. SEM images were obtained and the features of the roughness of the coating surfaces after deposition for 10, 20, 30 and 60 s were studied. It was found that co-deposition of tin-copper alloys and tin-copper-ultradisperse diamond particles increases the value of the limiting current from 2.8 · 10–2 to 5.0 · 10–2 A/cm2. With an increase in electrocrystallization over-voltage, the rate of nucleation increases and their size decreases, while ﬁne-grained and dense deposits are formed. With an increase in the deposition duration, crystallites grow and gradually coalesce with each other, the value of the equivalent diameter of the grain coatings increases, respectively, for: Sn – from 1 ⋅ 10–6 to 4 ⋅ 10–6 m, Sn-Cu – from 0.3 ⋅ 10–6 to 1.3 ⋅ 10–6 m, Sn-Cu-ultradispersed diamond – from 0.9 ⋅ 10–6 to 1.4 ⋅ 10–6 m. The established patterns make it possible to control the structure of the coatings and obtain deposits with speciﬁed properties. The presented results may be of interest to specialists involved in the formation of solderable galvanic coatings.